Composition, growth and condition index for a population of Poecilia reticulata (Pisces: Poeciliidae), in a pond in Heredia, Costa Rica - Urriola Hernández, Mario (2003)
A pond population of Poecilia reticulata was studied in Santo Domingo, Heredia, Costa Rica, between September and November of 1998. The sex ratio was 1:0.49 (males:females). The mean total length was 34.43 ± 7.26 mm for females, 23.50 ± 2.24 mm for males and 12.27 ± 3.41 mm for juveniles. The mean total weight was 0.69 ± 0.48 g for females; and 0.16 ± 0.05 g for males and 0.026 ± 0.027 g for juveniles. The total length-weight relationship for the total population was P= 6 ± 10 -5 Lt 3.3272 (r2 = 0.9613). The condition index equation was K = 25.755 e0.004Lt (r2 = 0.8925) for females and K=26.767 e0.003Lt (r2 =0.907) for males. The mean condition index was 31.29 ±0.55% for females and 28.52 ± 0.19% for males. Both sexes reached the sexual maturity when the males and females overcame the 20.00 mm and 23.5 mm of Lt respectively.